Dielectric and piezoelectric properties of modified lead-free NaNbO3–KNbO3/PVDF composite ceramics - Y. I. Yurasov (World Scientific Publishing, 2021)
This work presents the results of study of the electrophysical properties of composite polymer ceramics (1 − x)[KNN-LTSN]–xPVDF at x = 25 vol.% and x= 50 vol.% in the temperature range of T = 20–160∘C and frequency range of f = 2 × 101–2 × 106 Hz. The concentration dependence of piezomodules of the studied materials has been analyzed as a function of temperature. X-ray measurements have also been carried out. A model of description of revealed dielectric parameters dispersion in the material is presented. The nonclassical modified Havriliak–Negami model written for complex electrical conductivity has been used to describe the temperature–frequency properties. It is shown that the dielectric spectra of the studied composites include three relaxation processes in the temperature ranges of 40–80∘C, 80–120∘C and 120–150 ∘C, which were confirmed by the dynamics of changes in the dependences of γ′(f), tgδ(f), M′(f), M′′(f) and M′′(M′). All three processes are almost exactly described by this model and well correlated with the studies by other researchers of the composites based on PVDF. The results of this work show that the use of such experimental model is suitable for describing the complex dielectric spectra of any nonlinear dielectrics including composite materials.